Vertragliche Vereinbarungen als Instrument der Wirtschaftspolitik am Beispiel des Altschuldenkompromisses in der ostdeutschen Wohnungswirtschaft - Birgit Sander (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Relational contracts when employed as a tool of economic policy create mutual dependency between State and enterprises. This bluntly contradicts the principles of ,,Ordnungspolitik" as the key policy device to ensure efficiency on the microeconomic level and growth on the macroeconomic level. However, transaction cost theory points to potential transaction cost savings, hence efficiency improving features of relational contracting. The paper analyses the Performance of relational contracting between State and enterprises for the Special case of old debt agreements in east German housing. It discusses transaction characteristics and governance mechanisms as well as reasons, procedures and effects of contract adjustment. It concludes to which degree contractual and policy goals have been accomplished.
Keywords: D00; K12; R12; R31; 330; Wohnungspolitik; Wohnungsbaufinanzierung; Schulden; Privatisierung; Unvollständiger Vertrag; Transaktionskosten; Neue Bundesländer